Human molecular genetics - Strachan Tom; Read Andrew P (London Garland Science, 2004)
This book consists of four parts. Part One (Chapters 1-7) covers basic material on DNA structure and function, chromosomes, cells and development, pedigree analysis and the basic techniques used in the laboratory. Part Two (Chapters 8-12) discusses the v
Keywords: Human molecular genetics